Analysis Of Figurative Language In Three Poems By Robert Frost - Praja Nur Ichsan; Ammar Muhammad Ra’id Zhafir Nur Haqiqi Riyadi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research examines how Robert Frost uses metaphorical language in three of his well-known poems: "The Road Not Taken," "My November Guest," and "Stopping by Woods on a Snowy Evening." Personification, metaphor, symbol, exaggeration, and repetition are all often used, as the analysis makes clear. Personification is the most common figure of speech among them, lending human characteristics to inanimate things or abstract concepts in each of the three poems. This technique enhances the emotional impact of the poems and allows readers to connect more deeply with the themes and settings. The analysis of each poem explores how specific figures of speech contribute to the overall meaning. In "The Road Not Taken," metaphor and personification are used to explore the impact of life choices. "My November Guest" relies heavily on personification to portray melancholy and the beauty of autumn. "Stopping by Woods on a Snowy Evening" uses personification, hyperbole, symbol, and repetition to create a sense of isolation and reflection amidst natural beauty. Ultimately, Frost's masterful use of figurative language elevates the meaning of these poems, allowing readers to explore deeper interpretations beyond the literal text. This exemplifies his skill as a poet who effectively conveys the complexities of human experience and the natural world.